Changes in Pain and Psychosocial Functioning and Transition to Chronic Pain in Pediatric Sickle Cell Disease: A Cohort Follow-up Study. Issue 6 (June 2020) - Sil, Soumitri; Cohen, Lindsey L.; Bakshi, Nitya; Watt, Amanda; Hathaway, Morgan; Abudulai, Farida; Dampier, Carlton
Abstract : Objectives: This study aimed to: (1) examine changes in pain, psychosocial functioning, and health care utilization among children and adolescents with sickle cell disease (SCD) over a 2-year period and (2) identify baseline biopsychosocial variables associated with the development and maintenance of chronic SCD pain at follow-up. Materials and Methods: Forty-two youth (8 to 18 y old) with SCD completed a battery of self-report measures at baseline and 2-year follow-up. Analgesic, Anesthetic, and Addiction Clinical Trial Translational Innovations Opportunities and Networks and American Pain Society Pain Taxonomy (AAPT) diagnostic criteria were used to categorize patients into pain frequency groups at both timepoints: chronic (pain on most [≥15] d/mo for the past 6 mo, per AAPT diagnostic criteria), episodic (pain on 1 to 14 d/mo), or asymptomatic (0 d/mo). Results: At baseline, 31% (n=13) had chronic pain, 50% (n=21) episodic pain, and 19% (n=8) were asymptomatic. At follow-up, 40.5% (n=17) had chronic pain, 52.4% (n=22) episodic pain, and 7.1% (n=3) were asymptomatic. Between baseline and 2-year follow-up, 12% (n=5) developed chronic SCD pain. Depressive symptoms and admissions for pain significantly increased over time for youth with chronic pain ( P s<0.05). An interaction effect revealed that baseline pain groups differed in their change in pain intensity over time ( P <0.01). Baseline psychosocial factors (ie, higher functional disability, greater depressive symptoms, higher pain catastrophizing, and lower quality of life) were significantly associated with chronic pain at follow-up. Discussion: Biopsychosocial factors may be associated with the development and maintenance of chronic SCD pain and their relative contributions warrant further study. Abstract : Supplemental Digital Content is available in the text.